Neonicotinoid exposure disrupts bumblebee nest behavior, social networks, and thermoregulation - Crall, James D; Switzer, Callin M; Oppenheimer, Robert L; Ford Versypt, Ashlee N; Dey, Biswadip; Brown, Andrea; Eyster, Mackay; Guérin, Claire; Pierce, Naomi E; Combes, Stacey A; de Bivort, Benjamin L (Science (American Association for the Advancement of Science), 2018)
Neonicotinoid pesticides can negatively affect bee colonies, but the behavioral mechanisms by which these compounds impair colony growth remain unclear. Here, we investigate imidacloprid's effects on bumblebee worker behavior within the nest, using an automated, robotic platform for continuous, multicolony monitoring of uniquely identified workers. We find that exposure to field-realistic levels of imidacloprid impairs nursing and alters social and spatial dynamics within nests, but that these effects vary substantially with time of day. In the field, imidacloprid impairs colony thermoregulation, including the construction of an insulating wax canopy. Our results show that neonicotinoids induce widespread disruption of within-nest worker behavior that may contribute to impaired growth, highlighting the potential of automated techniques for characterizing the multifaceted, dynamic impacts of stressors on behavior in bee colonies.